Religion/Theology: Comparative Analysis of Islamic Satan and Miltonic Satan in Paradise Lost 1667. - Khan, Aziz Ullah (International Journal of Applied and Scientific Research, 2023)
This research will analyze the same share of Christianity and Islam in the interested ground of John Milton's "Paradise Lost" 1667 about human origin and fall (from heaven to earth) and first man temptation, disobedience and fall and as well as Satan standing, challenges and as rebellious in God's kingdom.